A global fund for social protection: Lessons from the diverse experiences of global health, agriculture and climate funds - Nicola Yeates; Chris Holden; Roosa Lambin; Carolyn Snell; Nabila Idris; Sophie Mackinder (International Labour Organization (ILO), 2023)
The recent social, ecological and economic crises have not only revealed the gaps in social protection systems across the world, but also drawn global attention to the ways in which international financial architectures have failed to support the development of universal social protection systems and floors. Within this context, this paper examines the idea of a global fund for social protection (GFSP) which has emerged as a potential solution to these structural failings. By drawing on the experiences of seven global funds across the health, climate, and agriculture sectors, the aim of this working paper is to identify key lessons that can guide the possible implementation of a prospective GFSP. Through a careful analysis of the governance structures, norms and standards of these funds, the paper makes certain recommendations to be taken into consideration if a GFSP is to be developed and implemented in the future.
Keywords: 330